(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
This article is devoted to identifying the key prerequisites and patterns necessary to justify the creation of an effective model of special (military-applied) physical training for operational-level officers. The analysis is based on the synthesis of modern scientific approaches, advanced practical experience, and specific physiological and functional requirements arising under operational-tactical conditions. In order to scientifically substantiate the structure and content of the proposed model, as well as to validate the identified prerequisites, an expert survey was conducted. A total of 29 highly qualified military specialists of the Armed Forces of Ukraine participated in the survey, including senior command-level officers with professional qualifications in the field of defense. The military personnel involved in the expert evaluation possess many years of service experience, a deep understanding of combat missions, modern tactics, and systemic personnel training. Experts were selected based on specific criteria: relevant higher education, experience in military physical training, scientific publications, or participation in the development of regulatory documents. Data collection was carried out using a structured questionnaire with a ranking scale. Statistical processing was performed using the Friedman test and Kendall’s coefficient of concordance. The results of the Friedman rank dispersion analysis revealed statistically significant differences among expert evaluations (χ² = 90.29; p < 0.001), and Kendall’s coefficient of concordance was (W = 0.705; p < 0.001), indicating a high level of agreement among the experts. According to the obtained data, the most significant components of special (military-applied) physical training for operational-level officers were identified as: team interaction (mean rank 7.7), stress resilience (7.3), response to combat stress (6.8), situational adaptability (5.9), and the development of cognitive abilities (4.9). The proposed model is aimed at the comprehensive development of the officers’ physical and functional qualities, ensuring their readiness to perform tasks of varying complexity under high physical and psycho-emotional stress in accordance with modern military standards.